Assessing Resilience of an Urban Neighborhood - Akbar Zargar; Zahra Ahari; Fatima Razeghi (صفه)
Vulnerability of cities has drastically increased over the recent decades. Disaster mitigation has also evolved to include a more holistic approach. The emphasis on strengthening single buildings has now shifted towards creating sustainable resilient cities, which incorporates physical, economic and social aspects. One such approach is the Disaster-Resistant Communities (DRC) Model. This Model has the potential to be used as the basis for assessing the resilience of cities and/or their vulnerability. This paper attempts to further develop the DRC Model, in combination with other existing models such as the three-dimensional city vulnerability matrices, to develop a framework for assessing neighborhood resilience. The resulting model is applied to Harzevil Neighborhood, Manjil, which was razed to the ground in Gilan and Zanjan Earthquake of 1990. This model assesses the resilience of this neighborhood in case of another hypothetical seismic jolt. The results indicate that despite its significant physical vulnerability, currently this neighborhood has substantial socioeconomic resilience. This means that its social capital has to be drawn upon to reduce its physical vulnerability.